Single phase inverter using Unipolar Sinusoidal Pulse Width Modulation - Arira, Talsya Kireina Bungsu; Asnil (Department of Electrical Engineering Universitas Negeri Padang, 2025)
As the population grows and energy demands increase, various resources are needed, including human resources, fossil-based natural resources, and renewable energy sources. An inverter is a crucial device in electrical power generation systems, functioning to convert direct current (DC) voltage into alternating current (AC) voltage in optimizing the performance of the inverter. An efficient switching method can reduce switching losses, minimize electromagnetic interference (EMI), allow the use of smaller filters, and result in lower Total Harmonic Distortion (THD). This research focuses on the simulation of a single-phase inverter employing the unipolar Sinusoidal Pulse Width Modulation (SPWM) technique. The working principle of SPWM involves comparing a reference waveform with a carrier waveform using a comparator in order to generate an ideal sinusoidal output., it was found that this switching technique is capable of producing an output waveform that closely resembles a sinusoidal wave. Without the use of an LC filter, the Total Harmonic Distortion (THD) was relatively high, reaching 120.27% at a frequency of 50 Hz. However, after applying an LC filter in a series-parallel configuration, the THD was successfully reduced to 14.78% at a frequency of 55 Hz. This demonstrates that the combination of the unipolar SPWM method and an LC filter is effective in improving the quality of the inverter output power and significantly reducing harmonic distortion.